Potential Synergism between Entomopathogenic Fungi and Entomopathogenic Nematodes for the control of false codling moth (Thaumatotibia leucotreta) - Prinsloo, Samantha Lee (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
False codling moth, Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) (FCM), is a major phytosanitary pest of citrus in South Africa. Sufficient control measures for the soil-dwelling life stages of FCM have yet to be identified and owing to restrictions on the use of insecticides, non-chemical control options have been investigated including the use of entomopathogenic fungi (EPF) and entomopathogenic nematodes (EPN). Laboratory and field trials on an indigenous EPF, Metarhizium anisopliae FCM Ar 23 B3, have shown that this isolate is capable of inducing mortality in FCM soil-dwelling life stages. Other agents that have been highlighted as potential controls for soil-dwelling FCM life stages are the EPN species Steinernema yirgalemense 157-C, S. jeffreyense J194 and H. noenieputensis 158-C. This study conducted laboratory bioassays to assess the virulence of these four control agents on fifth instar FCM, in 24-well plates. These results reaffirmed the virulence of the four microbial control agents at their recommended doses of 50 IJs (EPN) and 1Ã—107 conidia/ml (EPF) against fifth instar FCM with 80 to 96% larval mortality recorded. The EPF isolate exhibited the lowest mortality whilst S. yirgalemense induced the greatest mortality. In addition, the lethal concentration (LC) values for each isolate were determined using dose response bioassays. These values were previously unknown for all EPN species and for the EPF isolate based on the methodology used in this study. The LC50 results in order from lowest to highest EPN IJ concentration requirements were 4.38 IJs (S. yirgalemense), 4.47 IJs (S. jeffreyense) and 7.11 IJs (H. noenieputensis). The EPF isolate exhibited an LC50 of 3.42Ã—105 conidia/ml. Lastly, research has shown that the combination of two control agents may increase control of late instar lepidopteran and coleopteran larvae, through synergistic interactions. Thus, the interactions that occurred between the combination of these EPN species with the EPF isolate were determined. This study found that when all three EPN species were combined simultaneously and sequentially with the EPF isolate M. anisopliae FCM AR 23 B3, additive interactions took place with exception of the simultaneous application of S. yirgalemense and H. noenieputensis, with the EPF and S. jeffreyense applied 24 h post EPF application. For the former, a synergistic interaction was found, whilst for the latter two, an antagonistic interaction. Although no strongly synergistic interactions were observed, additive interactions have been shown to reach a synergistic level when certain parameters are changed. Moving forward, a uniform methodology for conducting EPF/EPN interaction experiments has been suggested. It has also been recommended that due to the additive interactions observed in this study, laboratory soil-bioassays and field trials should be carried out for all three EPN species in combination with the EPF isolate. This research will inevitably facilitate the constant knowledge into management strategies for the phytosanitary pest, FCM in South African citrus.
Keywords: Cryptophlebia leucotreta; Entomopathogenic fungi; Insect nematodes; Citrus -- Diseases and pests; Cryptophlebia leucotreta -- Biological control; Pests -- Integrated control; Biological pest control agents